Cranial reconstruction using computer designed polieteretercetone implant - Casallo Quiliano, Carlos Arturo (2010)
Background: Craneoplasty has 2 purposes; protection of the brain and a satisfying cosmetic result. There are different alloplast grafts to cranial reconstruction. Clinical case: A decompressive craniectomy was performed in a 29 years old man who had a severe brain trauma one month before admission. Clinically he is in coma, with a left large skull defect. After two months the patient is underwent to cranial reconstruction using computer designed polyetheretherketone implant, without complications related to surgery until now. Conclusion: Craneoplasty using computer designed PEEK implant is safe, offers great adaptability and biocompatibility, and minor surgical time.